Generation of the short TRIM32 isoform is regulated by Lys 247 acetylation and a PEST sequence. - Juncal Garcia-Garcia; Katrine Stange Overå; Waqas Khan; Eva Sjøttem (PLoS ONE, 2021)
TRIM32 is an E3 ligase implicated in diverse biological pathways and pathologies such as muscular dystrophy and cancer. TRIM32 are expressed both as full-length proteins, and as a truncated protein. The mechanisms for regulating these isoforms are poorly understood. Here we identify a PEST sequence in TRIM32 located in the unstructured region between the RING-BBox-CoiledCoil domains and the NHL repeats. The PEST sequence directs cleavage of TRIM32, generating a truncated protein similarly to the short isoform. We map three lysine residues that regulate PEST mediated cleavage and auto-ubiquitylation activity of TRIM32. Mimicking acetylation of lysine K247 completely inhibits TRIM32 cleavage, while the lysines K50 and K401 are implicated in auto-ubiquitylation activity. We show that the short isoform of TRIM32 is catalytic inactive, suggesting a dominant negative role. These findings uncover that TRIM32 is regulated by post-translational modifications of three lysine residues, and a conserved PEST sequence.